Drivers of Oxygen Consumption in the Northern Gulf of Mexico Hypoxic Waters—A Stable Carbon Isotope Perspective. Issue 19 (4th October 2018) - Wang, Hongjie; Hu, Xinping; Rabalais, Nancy N.; Brandes, Jay
Abstract: We examined the stable carbon isotopic composition of remineralized organic carbon (δ 13 COCx ) in the northern Gulf of Mexico (nGoM) using incubations (sediment and water) and a three‐end‐member mixing model. δ 13 COCx in incubating sediments was −18.1‰ ± 1.3‰, and δ 13 COCx in incubating near‐surface and near‐bottom waters varied with salinity, ranging from −30.4‰ to −16.2‰ from brackish water to full‐strength Gulf water. The average δ 13 COCx was −18.6‰ ± 1.8‰ at salinity >23. A three‐end‐member mixing model based on a multiyear data set collected in previous summer hypoxia cruises (2011, 2012, 2014, 2015, and 2016) suggested that δ 13 COCx in near‐bottom waters across the nGoM (5–50 m) was −18.1‰ ± 0.6‰. The close agreement of δ 13 COCx obtained from the three independent approaches, that is, incubations of water column, surface sediments, and mixing model, suggests that 13 C‐enriched organic matter of marine origin played the dominant role in near‐bottom water and benthic oxygen consumption in the nGoM shelf in summer. Plain Language Summary: Bottom water hypoxia, that is, dissolved oxygen concentration < 2 mg/L, has been increasingly disrupting important coastal ecosystems. The ultimate reasons for causing the low oxygen levels include stratified physical conditions that isolate bottom water from oxygen‐rich surface water and rapid respiration in the bottom water, where microbes feed on organic matter (OM) and at the same time consume oxygen. In complex coastal environments, OM can be supplied from multiple sources, including river delivery, coastal erosion, and primary production enhanced by terrestrial nutrient loading. On the Louisiana shelf of the northern Gulf of Mexico, where extensive summer hypoxia has been frequently observed, the type of OM that fuels bottom water oxygen consumption on a broad scale has not been systematically examined. Using field data and lab experiments, we address the question regarding the OM source issue on the Louisiana shelf. Our findings suggest that respiration of terrestrial OM is restricted to a low‐salinity zone where river influence is significant, while marine‐generated OM is dominant in the much broader Louisiana shelf. As the marine production is closely associated with land‐derived nutrients, curbing the hypoxia problem requires unambiguous and persistent management in fertilizer usage upstream. Key Points: δ 13 C of remineralizing organic carbon in summertime near‐bottom waters of the northern Gulf of Mexico was −18.1‰ ± 0.6‰ Water column δ 13 C of remineralized organic carbon varied along the salinity gradient 13 C‐enriched organic carbon remineralization dominated summertime near‐bottom water and benthic respiration